Traditional Tests for Implication of Terms Prevail in Singapore Despite ‘Acceptance’ of Belize Test: Sembcorp Marine Ltd v PPL Holdings Pte Ltd - GOH, Yihan (Institutional Knowledge at Singapore Management University, 2012)
There is an ongoing legal debate concerning the test governing the implication of terms in fact, prompted in no small measure by Lord Hoffmann’s influential speech in Attorney General of Belize v Belize Telecom. In Belize, Lord Hoffmann famously said that the question for a court considering whether a term should be implied is ‘whether such a [term] would spell out in express words what the instrument, read against the relevant background, would reasonably be understood to mean’. This has generally been regarded by judges3 and academics4 as subsuming the implication of terms within the broader rubric of ‘interpretation’. The consequence is that the ‘reasonable person’ test that underpins contractual interpretation now applies to determine whether a term should be implied.